Microwave-Assisted Extraction of Phytochemicals in Cogongrass (Imperata cylindrica) Rhizome - N. P. Minh (Journal of Global Pharma Technology, 2019)
Microwave irradiation has received a lot of attention. It is a feasible green solvent extraction method as it utilizes water or alcohols at elevated temperature and controlled pressure conditions. Microwave extraction emerges as a promising technique from an economical point of view, being inexpensive, simple and efficient. Cogongrass (Imperata cylindrica) rhizome is a good source of antioxidants such as phenolic, flavonoid and saponin. The rhizome-root part serves as traditional medicine for the treatment of a wide range of infections.  In our research, different parameters such as power of microwave (50, 75, 100, 125, 150 W), frequency of microwave (15, 20, 25, 30, 35 GHz), duration of the microwave irradiation (1.5, 2.0, 2.5, 3.0, 2.5 min), ratio of liquid to solid (water: material, 1.0:1.0, 1.5:1.0, 2.0:1.0, 2.5:1.0, 3.0:1.0), extraction temperature (70, 75, 80, 85, 90oC), number of extraction cycles (1, 2, 3, 4, 5) affecting to the microwave-assisted extraction of phytochemicals in cogongrass (Imperata cylindrica) rhizome were examined. Total total phenolic (mg GAE/ 100g), total flavonoid (mg GE/ 100g), saponin (%) were important indicators to identify the optimal variable. Our results showed that microwave power 100 W, frequency 30 GHz, duration 2.5 min, liquid to solid ratio 2.0:1.0, temperature 75oC, 3 cycles of extraction were appropriate for extraction of phytochemical components inside cogongrass (Imperata cylindrica) rhizome.Keywords: Cogongrass, Imperata cylindrica, Rhizome, Microwave, Extraction, Phenolic, Flavonoid, saponin.